Salvianolic acid B inhibits the development of diabetic peripheral neuropathy by suppressing autophagy and apoptosis - Wang, Qian-Qian; Zhai, Cui; Wahafu, Alafate; Zhu, Yan-Ting; Liu, Yong-Hui; Sun, Lian-Qing (Journal of pharmacy and pharmacology, 2019)
The aim of this study was to evaluate the neuroprotective effects of SalB on high glucose (HG)-induced excessive autophagy and apoptosis in vitro. The proliferation and apoptosis of RSC96 cells were determined using the MTT assay and flow cytometry, respectively. Western blot analysis was performed to examine the expression of autophagy and apoptosis-related proteins. RT-PCR and flow cytometry were manipulated to examine the level of Bcl-2. The signals of autophagy markers were detected using immunofluorescence methods. We found that HG significantly reduced RSC96 cell's proliferation and induced apoptosis. What's more, HG increased the level of autophagy and apoptosis-related proteins. However, these effects were reversed by SalB. In addition, we also found that 3-MA decreased the expression of LC3A/B and Beclin1, while the JNK inhibitor SP600125 reduced the levels of phosphorylated JNK, LC3A/B and Beclin1. High glucose not only induced apoptosis but also caused autophagic cell death by activating the JNK pathway. These effects prevented by SalB in an opposite manner.